Produção escrita e ensino comunicativo: análise de tarefas pedagógicas do material didático de um curso livre - Charão, Larissa Borges (Universidade do Vale do Rio dos Sinos, 2016)
This paper aims to analyze the writing tasks from the textbook of a language course in order to verify to what extent they relate to the communicative methodology proposed by the school. Based on the perspective that learning a language is learning how to use it to interact in different social contexts, the pedagogical tasks should express in their statements information regarding the position of the author, the interlocutor, as well as the purpose of language use. The results show that, out of the six tasks analyzed, three are satisfactorily aligned to the vision of language as social practice, since they present coherent purposes and clear information on the author’s position and interlocutor. The other three tasks, however, need adaptation to align more strongly to this view, because they don’t express purposes and interlocutors in an appropriate way.
Keywords: Ensino comunicativo; Tarefas de produção escrita; Língua Inglesa; Communicative approach; Writing tasks; English